Pengembangan media pembelajaran AIKO berbasis aplikasi android dari PowerPoint materi pertumbuhan dan pembangunan ekonomi kelas XI - Nazilatul Muharrami Nasifa; Ro’ufah Inayati (Universitas Negeri Malang, 2021)
Abstract Being in the industrial era 4.0, teachers as educators are required to understand technology more than their students. Teachers need to understand students' needs for technological developments so that classroom learning runs well. The development of learning media is one of the alternative solutions that can be used by teachers to meet the needs of students for technological developments. The purpose of research and development is to produce learning media products based on android applications from Microsoft PowerPoint on material for economic growth and development for class XI. This research and development uses the ADDIE model. The results of the research and development were obtained from the results of the feasibility test through filling out validation questionnaires with validators of material experts (lecturers), media experts (lecturers), learning practitioners (economics teachers), and test results with users (students) through small group trials and large group trial. The average result of the validation and testing as a whole obtained a score of 92.177 percent so that this research and development product is very valid and very feasible to be used as a learning medium. Abstrak Berada pada era industri 4.0 guru sebagai pendidik diharuskan untuk memahami teknologi lebih dari siswanya. Guru perlu memahami kebutuhan siswa atas perkembangan teknologi agar pembelajaran di kelas berjalan dengan baik. Pengembangan media pembelajaran menjadi salah satu solusi alternatif yang bisa digunakan oleh guru untuk memenuhi kebutuhan siswa atas perkembangan teknologi. Tujuan dari penelitian dan pengembangan adalah untuk menghasilkan produk media pembelajaran berbasis aplikasi android dari Microsoft PowerPoint pada materi pertumbuhan dan pembangunan ekonomi kelas XI. Penelitian dan pengembangan ini menggunakan model ADDIE. Hasil dari penelitian dan pengembangan diperoleh dari hasil uji kelayakan melalui pengisian kuisioner validasi bersama validator ahli materi (dosen), ahli media (dosen), praktisi pembelajaran (guru ekonomi), dan hasil uji coba bersama pengguna (siswa) melalui uji coba kelompok kecil dan uji coba kelompok besar. Rata-rata asil validasi dan uji coba secara keseluruhan memperoleh skor sebesar 92,177 persen sehingga produk penelitian dan pengembangan ini sangat valid dan sangat layak untuk digunakan sebagai media pembelajaran.